22 GHz H2O maser survey towards 221 BGPS sources. Issue 4 (15th September 2015) - Xi, Hongwei; Zhou, Jianjun; Esimbek, Jarken; Wu, Gang; He, Yuxin; Ji, Weiguang; Tang, Xiaoke
Abstract: We performed a 22 GHz H2 O maser survey towards 221 Bolocam Galactic Plane Survey (BGPS) sources. We detected 107 H2 O masers, of which 12 are new. The detection rate is 48.4 per cent for our sample. We obtained the positions of five new H2 O masers via On The Fly (OTF) observations. The detection rate of H2 O masers is correlated with continuum emission fluxes of BGPS sources at far-infrared, sub-millimetre and millimetre wavelengths. We employed the classification of Dunham et al. to classify the evolutionary stage of BGPS sources into Group 0, 1, 2, and 3. The detection rate and velocity range of H2 O masers increases as the BGPS sources evolve from Group 1 to Group 3. The BGPS sources associated with both H2 O and CH3 OH masers are more compact than that associated with either only H2 O or only CH3 OH masers. This indicates that the sources associated with both H2 O and CH3 OH masers are in relative later evolutionary stage. The detection rate of H2 O masers towards BGPS sources displaying evidence of the collapse phenomenon is 62.1 per cent, which suggests that most BGPS sources showing indications of collapse phenomena contain ongoing active star formation activities.